BENTUK ETNOMATEMATIKA PADA BATIK ADIPURWO DALAM PEMBELAJARAN POLA BILANGAN - Erni Puji Astuti; Riawan Yudi Purwoko; Medita Wahyu Sintiya (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2019)
Learning mathematics with cultural nuances (ethnomathematics), will be more meaningful for students in understanding mathematical concepts. One of the local cultures that is a pride in Purworejo is batik. Therefore, batik can be used as a medium for learning mathematics based on ethnomathematics. In this article we will explain the learning of mathematics using cultural backgrounds, namely the pattern of numbers using Adipurwo batik media typical of Purworejo, Central Java. The purpose of this article is to find out the ethnomathematics of Adipurwo batik motifs that are used as a medium of mathematics learning in material pattern numbers. Students can determine the pattern of numbers with Adipurwo batik media. The results in this study are as follows: the geblek and clanting motifs have different arithmetic sequence patterns with 6, while the pare and clorot leaf motifs have an arithmetic sequence pattern with differences 3. With the relationship between the number pattern and Adipurwo batik, mathematics learning will become more meaningful and more interesting, so students can understand mathematics easily and pleasantly.